Using signal-space concept to determine system performance of M-ary signaling - Yang, Hao Ran (Nanyang Technological University, 2024)
This report delves into the exploration of the signal-space concept, a fundamental framework in communication theory, to thoroughly examine and assess the system performance of M-ary signaling techniques. This investigation particularly focuses on two prominent modulation schemes: M-ary Phase Shift Keying (PSK) and M-ary Quadrature Amplitude Modulation (QAM). By leveraging the rich mathematical formulas and geometric representation offered by signal space, we aim to delve deep into the intricacies of these modulation techniques. Through meticulously crafted MATLAB simulations, we embark on a comprehensive analysis of bit error rate (BER) and symbol error rate (SER) as a function of signal-to-noise ratio (SNR). This meticulous investigation enables us to unravel the nuanced performance characteristics inherent in M-ary PSK and QAM schemes. By scrutinizing the behavior of these modulation schemes across varying SNR conditions, we gain invaluable insights into their error rate in Additive White Gaussian Noise (AWGN) communication scenarios. Moreover, beyond mere numerical analysis, our exploration extends to the visualization and interpretation of signal constellations within the signal-space domain. By examining the geometric arrangement of signal points on the constellation plane, we unravel the underlying principles governing the modulation process. This geometric perspective not only facilitates a deeper understanding of the modulation schemes but also paves the way for innovative design strategies aimed at optimizing performance metrics such as error rate and spectral efficiency. In essence, this report serves as a gateway to the world of signal-space analysis in the realm of M-ary signaling. Through rigorous experimentation and theoretical exploration, we endeavor to explore the intricate interplay between bit error rate (BER), symbol error rate (SER), and signal-to-noise ratio (SNR), ultimately paving the way for enhanced communication systems with improved performance and reliability.